2023
DOI: 10.1111/josi.12589
|View full text |Cite
|
Sign up to set email alerts
|

Families in quarantine: COVID‐19 pandemic effects on the work and home lives of women and their daughters

Emily F. Coyle,
Megan Fulcher,
Konner Baker
et al.

Abstract: The onset of the COVID‐19 pandemic in March 2020 disrupted the lives of millions of US families, with rising unemployment and initial lockdowns forcing nationwide school and daycare closures. These abrupt changes impacted women in particular, shifting how families navigated roles. Even pre‐pandemic, US women were responsible for the majority of household labor and childcare, and daughters bore greater chore responsibility than sons. We surveyed 280 families early in the pandemic (Spring 2020) and another 199 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Shifting values regarding marriage and fertility may be influenced by modern societal notions, with women placing greater emphasis on personal desires and autonomous choices, leading to scepticism about and resistance to traditional views on marriage and fertility [ 60 , 61 ]. Last, the influence of family and social cultural beliefs can result in women’s assuming a greater burden of household chores and childcare responsibilities, preventing the equal division of labour and support [ 62 , 63 ] and thereby generating negative emotions. In conclusion, these factors collectively contribute to women’s negative emotions towards marriage and fertility, requiring further attention and exploration from relevant authorities.…”
Section: Discussionmentioning
confidence: 99%
“…Shifting values regarding marriage and fertility may be influenced by modern societal notions, with women placing greater emphasis on personal desires and autonomous choices, leading to scepticism about and resistance to traditional views on marriage and fertility [ 60 , 61 ]. Last, the influence of family and social cultural beliefs can result in women’s assuming a greater burden of household chores and childcare responsibilities, preventing the equal division of labour and support [ 62 , 63 ] and thereby generating negative emotions. In conclusion, these factors collectively contribute to women’s negative emotions towards marriage and fertility, requiring further attention and exploration from relevant authorities.…”
Section: Discussionmentioning
confidence: 99%
“…For example, flexible employer policies (e.g., working from home) may allow the type of fathering engagement that many of our participants described in the early months of COVID-19. Further, scholars are beginning to describe how policies that promote paid family leave, subsidized child care, and universal prekindergarten may provide an important safety net for families and equalize gender division of labor both at work and at home in a way that empowers, rather than constrain, father engagement (Coyle et al, 2023; Ooms, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…It also illustrates the gendered nature of work‐family conflict, flexibility in work requirements, and how the negative impacts of these forces may be borne out by this generation of youth who are exposed to lower‐quality parenting due to pandemic‐related stress and strain. The potential for intergenerational impacts is also identified in a study of almost 300 mothers using surveys and time‐use diaries (Coyle et al., 2023). As seen across other studies in this Special Issue, mothers reported an increase in work‐family conflict during the pandemic as compared to before the pandemic, and married mothers had more stress, worked more hours, but also had greater life satisfaction than unmarried mothers.…”
Section: Gendered Reorganization Of Division Of Labor Impacts Work Lifementioning
confidence: 97%
“…Caring for children and household chores are also often enacted by women, and healthy older family members were no longer able to support women in these responsibilities. Increased eldercare demands and decreased childcare support set the stage for empirical findings in this Special Issue that women experienced increased work versus family role conflict and burdens of household and childcare responsibilities (e.g., Bernhardt et al., 2022; Coyle et al., 2023; Dinella et al., 2023; Lee et al., 2022).…”
Section: Introductionmentioning
confidence: 99%